Analisis Laboratory Jargon dan Miskonsepsi dalam Materi Asam-Basa - Tritiyatma; Belgys; Yuli; Irma Ratna (Jurnal Riset Pendidikan Kimia (JRPK), 2018)
The purpose of this study is to analyze the Laboratory Jargon and misconception in acid-base learning on second grade high school students. The study involved the 320 of chemistry students in five secondary schools in Pulo Gadung district, East Jakarta. The research employed the quantitative survey method. Research data obtained through student answers on Laboratory Jargon Questionnaires, and interviews. The misconception discussed in this study relates to several concepts on acid-base in related to atoms and molecules, dissociation of water, ion formation, neutralization reaction, acid strength (pH), acid-base indicator, and water properties. The results of the research showed that from the ten questions in Laboratory Jargon Questionnaires are many students have misconceptions in relation to Laboratory Jargon. The percentage of student misconception on the average from the ten concepts is 64.44%. The biggest percentage of student misconception is on water amphoter concept that is 85,31% then acid strength (pH) is 75,62%. Based on the results of interviews most students chose the answer of misconception concepts because students are accustomed to learn a chemical concept with a Laboratory Jargon from teachers or other learning resources. Keywords Laboratory Jargon, misconception, acid-base, survey